The determination of post-exposure regrowth effects and the bactericidal activity of selected antimycobacterial agents against mycobacterium tuberculosis - Masango, Refilwe Winstance (My University, 2000)
Refer to document
Thesis (Msc. (Medical Sciences)) -- University of LImpopo, 2000
Keywords: Tuberculosis; Bactericidal activity; Anticimycobacterial agents; Mycobacterium tuberculosis -- South Africa.; Tuberculosis - Microbiology.